Estimation of Iron Availability in Modified Cereal β-Glucan Extracts by an in vitro Digestion Model - Marasca, Elena; Zehnder-Wyss, Olivia; Boulos, Samy; Nyström, Laura (Frontiers in Nutrition, 2022)
For cereal-based foods rich in dietary fibers, iron bioavailability is known to be poor. For native cereal β-glucan extracts, literature has demonstrated that the main factor impacting the bioavailability is phytic acid, which is often found in association with dietary fibers. During food processing, β-glucan can undergo modifications which could potentially affect the equilibrium between phytic acid, fiber, and iron. In this study, an in vitro digestion was used to elucidate the iron dialysability, and hence estimate iron availability, in the presence of native, chelating resin (Chelex)-treated, oxidised, or partially hydrolysed oat and barley β-glucan extracts (at 1% actual β-glucan concentration), with or without phytase treatment. It was confirmed that pure, phytic acid-free β-glucan polysaccharide does not impede iron availability in cereal foods, while phytic acid, and to a smaller extent, also proteins, associated to β-glucan can do so. Neither Chelex-treatment nor partial hydrolysis, 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO) or NaIO4 oxidation significantly influenced the phytic acid content of the β-glucan extracts (ranging 2.0–3.9%; p > 0.05). Consequently, as long as intrinsic phytic acid was still present, the β-glucan extracts blocked the iron availability regardless of source (oat, barley) or Chelex-treatment, partial hydrolysis or NaIO4-oxidation down to 0–8% (relative to the reference without β-glucan extract). Remarkably, TEMPO-oxidation released around 50% of the sequestered iron despite unchanged phytic acid levels in the modified extract. We propose an iron-mobilising effect of the TEMPO product β-polyglucuronan from insoluble Fe(II)/phytate/protein aggregates to soluble Fe(II)/bile salt units that can cross the dialysis membrane. In addition, Chelex-treatment was identified as prerequisite for phytase to dramatically diminish iron retention of the extract for virtually full availability, with implications for optimal iron bioavailability in cereal foods.